Chaim L. Pekeris and the Art of Applying Mathematics with WEIZAC, 1955–1963 - Corry, Leo; Leviathan, Raya (SpringerBriefs in History of Science and Technology, 2023)
IX, 123 p. 16 illus., 3 illus. in color.